Land potential for the development of settlement areas in East Halmahera Regency - Soentpiet, Nurhalis; Widiatmaka, Widiatmaka; Hidayat, Janthy T (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
A limit of potential land causes many problems to the land which lead to a regional development issues. Particularly, for the settlement. Besides, the increasing population is inversely proportional to the availability pf the land. Such situation has occurred in many areas, as well as in East Halmahera Regency. Therefore, this research aims to identify potential land for the settlement’s development through land suitability and land availability. The methodology used to in this study is Multi Criteria Evaluation (MCE). The indicators used are slope, flood inundation, landslide susceptibility, drainage, soil depth, soil texture and geology. Overlay between thematic maps, official spatial planning maps and land use maps is the methodology used for land availability. The result shows 2.356 hectare or 1,92% of land is Suitable (S1), 60.385 hectare or 9.52% is Suitable (S2), 21.632 hectare or 3.39% is Marginally suitable (S3) and 12.456 hectare or 1.93% is Not Suitable (N) for settlement development in Halmahera Regency.